Demystifying Digital Influence: TikTok and E-WOM in Shaping Purchase Intention via Brand Equity - Carandy, Jeany Aurieal Liberty; Dewi, Citra Kusuma (PT. EQUATOR SINAR AKADEMIA, 2025)
In the present paper, we aim to identify and analyze the influence of social media and e-WOM on purchase intention via brand equity, with a focus on the skincare brand Skintific in Indonesia. There has been conflicting evidence from studies that have looked at how social media and e-WOM influence customer behaviour, even if TikTok's marketing importance is on the rise. By suggesting brand equity as a mediating component, this study fills this gap. Data gathered from 411 TikTok users who follow material about beauty was analyzed quantitatively. The analysis was conducted using SEM-PLS. According to the results, using social media and e-WOM both increase brand equity. In addition to having a favourable effect on intent to buy, brand equity also acts as a mediator between the two sets of factors. This study adds to the body of knowledge on digital marketing by elucidating the mechanisms via which brand equity influences customer intentions within the personal care industry. It also offers practical insights for marketers seeking to optimize brand value and purchasing behavior through social media engagement.